2013
DOI: 10.1158/1078-0432.ccr-13-1337
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to CDK2 Inhibitors Is Associated with Selection of Polyploid Cells inCCNE1-Amplified Ovarian Cancer

Abstract: Purpose: Amplification of cyclin E1 (CCNE1) is associated with poor outcome in breast, lung, and other solid cancers, and is the most prominent structural variant associated with primary treatment failure in highgrade serous ovarian cancer (HGSC). We have previously shown that CCNE1-amplified tumors show amplicon-dependent sensitivity to CCNE1 suppression. Here, we explore targeting CDK2 as a novel therapeutic strategy in CCNE1-amplified cancers and mechanisms of resistance.Experimental Design: We examined the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 32 publications
10
72
0
Order By: Relevance
“…Ovarian cell lines with CCNE1 amplification show a specific dependency for maintenance of CCNE1 expression (5,6). We have validated CDK2 as a therapeutic target by showing selective sensitivity to suppression either by gene knockdown or using small molecule inhibitors (7), consistent with findings in breast cancer (8).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Ovarian cell lines with CCNE1 amplification show a specific dependency for maintenance of CCNE1 expression (5,6). We have validated CDK2 as a therapeutic target by showing selective sensitivity to suppression either by gene knockdown or using small molecule inhibitors (7), consistent with findings in breast cancer (8).…”
supporting
confidence: 74%
“…We have recently shown oncogene addiction to Cyclin E1 and its partner kinase, CDK2, in CCNE1-amplified ovarian tumors (7), suggesting that use of CDK2 inhibitors may be effective in these cancers. In addition to CDK2, Cyclin E1 interacts with CDK1 and CDK3 and has kinase-independent functions (4).…”
Section: Ccne1mentioning
confidence: 99%
“…Pelvic high-grade serous carcinoma (HGSC) of either tubo-ovarian or endometrial origin is an aggressive and deadly gynecological malignancy with few available targeted therapies, due in part to the absence of high-frequency oncogenic point mutations in drug target genes (1)(2)(3)(4). Recently, The Cancer Genome Atlas (TCGA) projects have advanced our understanding of the genomic landscape of ovarian and endometrial HGSC and confirmed a prevalence of somatic tumor protein p53 mutations and extensive copy number alterations, such as numerous DNA amplifications and deletions (1,5).…”
Section: Introductionmentioning
confidence: 99%
“…The major partner kinase of cyclin E, CDK2, phosphorylates Rb and displaces it from a complex with E2F1, which promotes E2F1-dependent transcription of BRCA1 and other DNA damage repair genes [6, 15]. To date, no drugs directly target cyclin E. Further, indirect targeting of cyclin E with currently available CDK2 inhibitors is limited by the development of chemoresistance that occurs in part through E2F1 upregulation [16, 17]. An alternate and emerging paradigm is to convert HR-proficient tumors to HR-deficient phenotypes by using epigenetic drugs [4, 9].…”
Section: Introductionmentioning
confidence: 99%